PENERAPAN PROJECT BASED LEARNING BERBANTUAN REWARD UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BERKARYA SENI GRAFIS SISWA - sri arisna, made (Universitas Pendidikan Ganesha, 2018)
This research is a classroom action research which aims to (1) to increase student activity of class IX.3 SMP Negeri 2 Singarajain even semester of academic year 2017/2018 through implementation of reward-assisted project based learning, and (2) to increase the activity of students of class IX.3 SMP Negeri 2 Singarajain even semester of academic year 2017/2018 in producing graphic arts trough the implementation of Reward-assisted Project Based Learning. The research subjects of this action are the students of class IX.3 SMP Negeri 2 Singarajaat Academic Year 2017/2018 with total number of 36 students. This Class Action Research Design (PTK) follows the model of Stephen Kemmis conducted in two cycles. Each cycle is held in three or two meetings with each meeting 2 X 40 minutes and 1 X 40 minutes. This research data was collected by observation sheet and project test. The collected data were analyzed descriptively qualitative and quantitative descriptive. The result of the research shows that (1) the Implementation of Reward-assisted Project Based Learning can increase the students 'activity in graphic arts learning. Before the action, the students' activity is quite active, the cycle I is still quite active (52%) and in cycle II is more active (89%), (2) the Implementation of Reward-assisted Project Based Learning can improve the achievement of graphic art work. Before the average score cycle is 69.00 (36% completeness). After the action in the first cycle achievement works graphic arts students average score of 75.36 (mastery 53%), while in the second cycle average score of 84.58 (92% completeness). Keywords: Project Based Learning, Reward, Activity, Activity, AchievementLearning